What are the needs of adolescents and young adults after a cancer treatment? a Delphi study - Galán, S.; De la Vega, R.; Tomé-Pires, C.; Racine, M.; Solé, E.; Mark, P, J.; Miró, J. (European Journal of Cancer Care, 2017)
Advances in the early detection of cancer and the development of more effective treatments have resulted in a larger number of adolescents and young adults (AYAs), becoming cancer survivors. However, knowledge regarding their needs and if those needs are adequately addressed remains limited. The aims of this study were to: (1) better understand the needs of AYAs after cancer treatment; (2) analyse the importance of those needs; (3) determine which needs are not adequately addressed; and (4) test the hypothesis that AYA cancer survivors have different needs than adult survivors. Twenty‐nine health oncology professionals, 17 AYA survivors and 12 relatives of AYA survivors participated in the Delphi study. The needs identified could be classified into six categories, and all were rated as highly important by all participants. The category perceived as least adequately addressed across the three groups was ‘Counselling and psychological support.’ The findings provide important new information regarding the needs of AYA cancer survivors that can inform the development of interventions to improve the quality of life of these individuals.